The prevalence of lymphoid follicles and intestinal metaplasia in Helicobacter pylori associated clinically significant gastroduodenal diseases - Vildan TAŞKIN; Elif GÜRER İNANÇ and Ramazan SARI and Abdullah AYDIN and Bülent YILDIRIM and Murat ALADAĞ and Fatih HİLMİOĞLU (Turkish Journal of Gastroenterology, 2019)
-